A direct peroral cholangioscopy‐assisted therapy for a choledochojejunostomy anastomotic stricture via EUS‐guided hepaticogastrostomy. (28th June 2020) - Mandai, Koichiro; Uno, Koji; Yasuda, Kenjiro
Abstract : Highlight Mandai et al describe their method of direct peroral cholangioscopy‐assisted therapy for a choledochojejunostomy anastomotic stricture through the endoscopic ultrasound‐guided hepaticogastrostomy route. Success with this method suggests that direct peroral cholangioscopy using an ultra‐slim endoscope may be an option for antegrade treatment through the endoscopic ultrasound‐guided hepaticogastrostomy route.